Dynamic estimation of an interest rate structure in Colombia. Empirical analysis using the Kalman filter - Maldonado Castaño, Rogelio (2014)
The official estimation for the term structure model in Colombia is based on the Nelson and Siegel (1987) development which is widely accepted and used. This estimation is based on the curve fitting with available data only for one day ahead making difficult to estimate the future zero-coupon yield curve. Taking into account the importance of having an estimation of the term structure for the valuation of financial assets in the Colombian market this research proposes a methodology to estimate in a dynamic form the parameters of interest rates in the Nelson and Siegel Model. This required the use of the reparameterization proposed by Diebold and Li (2006) which determines the shape of the term structure through latent factors such as level slope and curvature. This paper aims to show the dynamic estimation of the term structure of interest rate using the Kalman filter methodology framed in State - space. Results show that predictions are successful for more than one period in the future.